Indole Acetic Acid production by fluorescent Pseudomonas isolated from the rhizospheric soils of Malus and Pyrus - Kapoor, Ritika; Ruchi, Ruchi; Kumar, Ajay; Kumar, Amit; Patil, Sandip; Pratush, Amit; Kaur, Mohinder (Recent Research in Science and Technology, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> Fluorescent Pseudomonas, a major component of rhizobacteria, promote the plant growth through their multifarious activities. In the present investigations, thirty strains of fluorescent Pseudomonas were isolated from the rhizosphere of apple and pear plants of their normal and replant sites and found that the count of Pseudomonas strains were more in normal site as compare to replant site. They were screened for auxins production (indole acetic acid or IAA) and it was found that the strains isolated from normal sites produced more auxins (7-30 µg/ml) as compared to the isolates of replant site (1-4µg/ml). Four strains viz PN-4-SAN, PN-10-SAN, AN-2-NAG and AN-4-NAG were selected on the basis of their higher auxin production. The maximum production of IAA was observed at 72 h incubation period at pH 7.0 under shaken condition at 28oC. The highest IAA was produced by strain AN-2-NAG (30 µg/ml) and PN-4-SAN (30 µg/ml) isolated from Malus (Apple) and Pyrus (Pear) rhizosphere soil, respectively. An attempt was made to extract, purify and evaluate IAA by thin layer chromatography and specific bioassay method. The IAA (Auxin) produced by both the isolates i.e. AN-2-NAG and PN-4-SAN showed Rf value of 0.81. The partially purified and extracted auxins were evaluated by bioassay. The auxins produced by isolates AN-2-NAG and PN-4-SAN showed highest increased in length of coleoptiles of avena. These isolates could be potential strains for bioinoculant production for apple and pear.